Kesiapan Belajar Jarak Jauh Siswa SMP di Kota Malang - Wardhani, Ganesha Sekar Ayu; Purnomo, Agus; Wiradimadja, agung (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The Covid-19 pandemic has an impact on all aspects, including education. This pandemic also impacts education in Malang City, and the Education Office has implemented learning from home policy. However, implementation for two semesters shows that both the school and students are relatively not ready to be involved in distance learning activities. This article aims to look at the tendency of learning readiness to understand the material of Junior High School students in Malang City during distance learning. The quantitative survey approach answers questions that answer the purpose of this article. The calculation of Slovin determined student readiness data collected from all state Junior High Schools in Malang City as many as 400 people with a degree of error of 5%. The data technique uses an online questionnaire (google form). The data is managed through the editing, scoring, coding, and tabulating stages, which are the basis for conducting a cross-tabulation analysis. Field findings show that public Junior High School students in Malang City have a high level of learning readiness and tend to understand the material with an average percentage of 60%. The implications of these findings contribute to understanding the implementation of distance learning from the student's point of view regarding the aspect of readiness-recommendations for further research related to how distance learning is managed based on the existing readiness profile.